Optimization of synthetic domestic wastewater treatment performance in anoxic/aerobic sequencing batch reactor with zeolite addition - Gurtekin, Engin (Taylor & Francis Inc, 2023)
In this study, treatment performance was investigated based on chemical oxygen demand (COD), ammonium nitrogen (NH4+-N), total inorganic nitrogen (TIN) and simultaneous nitrification and denitrification (SND) parameters in a zeolite-added anoxic/aerobic sequencing batch reactor. Response surface methodology (RSM) was used to model treatment performance, determine the impact of operating conditions, and optimize them. The effect of zeolite size, dosage and COD/NH4+-N (C/N) ratio as operating parameters were evaluated in the central composite design (CCD). Variance analysis (ANOVA) results of the quadratic model, high coefficients of determination and low values of the root mean square error (RMSE) for dependent variables indicated the validity of the model in predicting experimental results. The desirability function showed that optimum conditions were 0.80 mm for zeolite size, 3.05 g/L for zeolite dosage and 9.8 for C/N. Under these conditions, the maximum COD, NH4+-N, TIN removal efficiencies and SND efficiency were 92.85%, 93.3%, 77.33% and 82.96%, respectively. The results of the study showed that the most effective independent variable on dependent variables was the C/N ratio.
Keywords: Anoxic; aerobic; C; N ratio; response surface methodology (RSM); simultaneous nitrification and denitrification (SND); zeolite